Perancangan Sistem Informasi Manajemen Rumah Sakit Modul Farmasi - Yulianti, Erna; Oka Sudana, A.A.K.; Ika Marini Mandenni, Ni Made (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi, 2015)
The Installation of Hospital Pharmacy still using conventional system, such as inventory control, recording transaction data, and preparing reports using Spreed Sheet Application that are not integrated with other modules so that cause difficulties in processing data. Hospital Management Information System Pharmacy Module needed to facilitate data processing and reports which previously still using conventional way, so that the information obtained become more rapid, precise, and accurate to improve the quality of hospital services. Stage of the system design was conducted by TAS, they are defining the initial scope, defining the requirements, designing the business process architecture, designing the system architecture, and evaluating architectures. Pharmacy module contains the Process of Master Data Management, Medicine Inventory Management, Drug Compounding, Selling Price Determination, Sales, and Reporting. Result of this system design are Context Diagram, Physical Data Model, Hierarchy Chart, Overview Diagram, Data Flow Diagram, User Interface Design, and Relation Modules.
Keywords: Rancangan; Sistem Informasi Manajemen Rumah Sakit; Modul Farmasi; Metode TAS